HE ROLE OF TELEMEDICINE IN TRAINING OF SCIENTIFIC-PEDAGOGICAL AND PROFESSIONAL MEDICAL STAFF - M.K. GULOV; D.K. MUKHABBATOV; K.K. KOBILOV; S.G. ALI-ZADE (Avicenna Tajik State Medical University, 2020)
Nowadays, telemedicine services are widely used throughout the world. Various types of telemedicine services, such as the storage and transmission of real-time information, remote monitoring or self-control can be applied in the fields of education, health and management, disease screening and disaster risk management worldwide. Telemedicine can play a big role in conducting medical research, as well as in the field of training scientific personnel, allowing remotely collaborate with scientific and clinical institutions and gain access to expensive remote equipment. In this context, it is considered appropriate to develop and apply such innovative ideas as online computing models in telehealth applications; simplified software and hardware interfaces, programs for modelling; portable telepresence systems; artificial intelligence applications that are especially relevant in cases where simulated patients cannot replace real ones; and development of a large number of application simulators.